1998
DOI: 10.1023/a:1024463406656
|View full text |Cite
|
Sign up to set email alerts
|

The development of a scale to assess war‐time atrocities: The war events scale

Abstract: The War Events Scale (WES) was developed to assist clinicians with the assessment of war zone veterans' exposure to, and participation in war-time atrocities distinct from combat, and their current distress from these events. Data concerning content validity, test-retest reliability, internal consistency, as well as correlational data with the Combat Exposure Scale and the Mississippi Scale are presented. Results indicate that the WES does have adequate internal consistency and test-retest reliability, and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Strikingly, test–retest reliability over a 1-week interval of the combat exposure scale, which also assesses combat event frequency on a similar Likert scale, was 0.97 in a sample of Vietnam veterans (Keane et al, 1989 ). High retest reliability coefficients of self-reported frequencies of war events and atrocities in a sample of military veterans ( r =0.83–0.87) were also observed by Unger, Gould, and Babich ( 1998 ) over a 4-week interval. Hence, the inconsistent results concerning reliability of self-reported event frequencies warrant further investigation.…”
Section: Assessing the Number Of Traumatic Event Types Versus Event Fsupporting
confidence: 59%
See 1 more Smart Citation
“…Strikingly, test–retest reliability over a 1-week interval of the combat exposure scale, which also assesses combat event frequency on a similar Likert scale, was 0.97 in a sample of Vietnam veterans (Keane et al, 1989 ). High retest reliability coefficients of self-reported frequencies of war events and atrocities in a sample of military veterans ( r =0.83–0.87) were also observed by Unger, Gould, and Babich ( 1998 ) over a 4-week interval. Hence, the inconsistent results concerning reliability of self-reported event frequencies warrant further investigation.…”
Section: Assessing the Number Of Traumatic Event Types Versus Event Fsupporting
confidence: 59%
“…The test–retest interval for the reliability analyses was relatively short, and future research should investigate whether the retrospective reports remain stable over longer time periods. Furthermore, similar to other studies measuring traumatic event frequency (Keane et al, 1989 ; Roemer et al, 1998 ; Unger et al, 1998 ), we assessed traumatic event frequency in categories as opposed to exact event frequencies. This decision was made since we observed that individuals with high trauma exposure had difficulties recalling the exact event frequencies but were able to provide categorical answers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the war atrocity data suggest still greater complexity in the etiology of DESNOS and PTSD. When the witnessing of atrocities was distinguished from participation in atrocities (Unger et al, 1998), DESNOS and PTSD were differentially related to atrocity exposure. Atrocity participation was a risk factor for DESNOS but not PTSD.…”
Section: Ptsd Desnos and Trauma Historymentioning
confidence: 97%
“…The selection and categorization of event-list items in previous research on exposure to political violence have commonly been carried out without an explicitly stated basis; however, from the frequently used strategy of selecting few items as indicators of exposure (e.g., Garbarino & Kostelny, 1996), the use of internal-consistency reliability tests (e.g., Miller et al, 2002;Orcutt, Erickson, & Wolfe, 2004;Roemer, Litz, Orsillo, Ehlich, & Friedman, 1998;Unger, Gould, & Babich, 1998) and application of factor-analytic techniques for item categorization (e.g., Kuterovac-Jagodic, 2003;Macksoud, 1992;Momartin, Silove, Manicavasagar, & Steel, 2002), it is apparent that assessment of exposure to political violence has commonly been based on an effect-indicator measurement model.…”
Section: The Basic Issue: Choice Of Measurement Modelmentioning
confidence: 99%